Effect of Stunting Education Counseling with Booklet Media on Parental Knowledge and Attitude As an Effort to Overcome Stunting - Triatmaja, Dendy; Lestari, Keri; Setiabudiawan, Budi (Journal of Maternal and Child Health, 2023)
Background: Stunting is developmental disorders experienced by children due to poor nutrition, repeated infections, and inadequate psychosocial stimulation. The problem of stunting in children under five shows an average rate of 35.3% in West Java. Stunting is a problem because it is associated with an increased risk of disease and death, suboptimal brain development, which results in delayed motor development and stunted mental growth. Jamika sub-district has a high prevalence of stunting under five in West Java, which is 23.7%. Pharmacists as Agents of Change can also optimize their role by providing information and education on stunting prevention. Subjects and Method: This study uses a design Pretest-posttest control group design at the Posyandu, Jamika Village, from February to April 2022. The total sample in this study was 30 people who were taken from mothers who had toddler 0-24 months of age. Samples were obtained by simple random sampling. The dependent attitudes of parents. The independent variable was knowledge. The data that has been collected is then analyzed using chi square test and odds ratio (OR). Results: Good knowledge increased the attitude of parents in efforts to overcome stunting at Posyandu, Jamaika village. Parents with good knowledge increased attitude by 1.40 times to have a positive attitude in efforts to overcome stunting, and this result is statistically significant (OR= 1.40; 95% CI= 0.87 to 2.23; p= 0.008). Conclusion: There was a relationship between good knowledge with attitude of parents as an effort to overcome stunting in the Posyandu, Jamika village with booklet media. Keywords: stunting, booklet, knowledge, attitudes, parents. Correspondence:Dendy Triatmaja. Master of Clinical Pharmacy Study Program.  Universitas Padjadjaran. Jl. Raya Bandung Sumedang KM 21, Jatinangor 45363. Email: dendy20001@unpad.ac.id. Mobile: 082250888878.